Comparing posaconazole and itraconazole for antifungal prophylaxis in critically ill lung transplant recipients: Efficacy and plasma concentrations. Issue 4 (14th July 2021) - Kallee, Simon; Scharf, Christina; Schroeder, Ines; Paal, Michael; Vogeser, Michael; Irlbeck, Michael; Zander, Johannes; Zoller, Michael; Jung, Jette; Kneidinger, Nikolaus; Schneider, Christian; Michel, Sebastian; et al.
Abstract: Background: Posaconazole and itraconazole are commonly used for systemic antifungal prophylaxis after lung transplantation. The aim of this study on critically ill lung transplant recipients was to assess the rate of adequate plasma concentrations and the frequency of fungal‐induced transitions from antifungal prophylaxis to therapy after the administration of either posaconazole or itraconazole for systemic prophylaxis. Methods: Critically ill lung transplant recipients with postoperative posaconazole or itraconazole prophylaxis and therapeutic drug monitoring from February 2016 to November 2019 were retrospectively included in the study. Positive fungal cultures or Aspergillus antigen tests resulting in a transition from antifungal prophylaxis to therapy were analyzed from the first day of prophylaxis until 7 days after the last sample for each patient. Adequate plasma concentrations were defined as ≥500 µg/L for itraconazole and ≥700 µg/L for posaconazole. Results: Two hundred seventy‐five samples from 73 patients were included in the analysis. Overall, 60% of the posaconazole and 55% of the itraconazole concentrations were subtherapeutic. Administration of posaconazole suspension resulted significantly ( P  < .01) more often in subtherapeutic concentrations than tablets (68% vs 10%). Patients treated with posaconazole showed less positive fungal records resulting in a transition from prophylaxis to therapy than patients treated with itraconazole (10% vs 33%, P ‐value: .029). The detection of a fungal pathogen was not associated with the measured plasma concentrations or the achievement of the target concentrations. Conclusion: Our findings suggest that posaconazole should be used instead of itraconazole for systemic prophylaxis in critically ill lung transplant recipients.